The Relationship Between Caregiver Stress and Health Anxiety with the Mediation of Emotional Expression in Caregivers of Patients with Chronic Illnesses Admitted to Military Hospitals in Tehran - Salari Doroudi, Neda; Bahrami, Bita (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to determine the relationship between caregiver stress and health anxiety with the mediation of emotional expression in caregivers of patients with chronic illnesses admitted to military hospitals in Tehran. Methods and Materials: This study employed a correlational research design using structural equation modeling (SEM). The study population consisted of all caregivers of patients with chronic illnesses admitted to military hospitals in Tehran during the first half of 2023. The sample size was 290 individuals, selected using convenience sampling. The research tools included the Novak and Guest Caregiver Stress Questionnaire (1989), the Salkovskis and Warwick Health Anxiety Questionnaire (2002), and the King and Emmons Emotional Expression Questionnaire (1990). The data were analyzed using structural equation modeling (SEM) with LISREL 8.54 and SPSS 24 software. Findings: The analysis of direct path coefficients revealed a significant direct relationship between caregiver stress (β = 0.23, p < 0.001) and emotional expression (β = -0.58, p < 0.001) with health anxiety. All model fit indices supported the acceptability of the structural model with the collected data (β = -0.42, p < 0.001). Conclusion: The study’s findings suggest that emotional expression can play an important role in reducing the negative effects of caregiver stress on the mental health of caregivers of patients with chronic illnesses.